Efficacy of Mometasone Furoate and Fluticasone Furoate on Persistent Allergic Rhinoconjunctivitis - W. Hamizan Aneeza M.S. (Allergy & Rhinology, 2013)
Allergic rhinoconjunctivitis denotes both nasal and ocular manifestation of allergy, which may be solely treated with intranasal steroid. This study compares the efficacy of mometasone furoate nasal spray (NS) and fluticasone furoate NS in treatment of allergic rhinoconjunctivitis. The secondary objective is to study the severity of baseline ocular symptoms in allergic rhinoconjunctivitis. Seventy-eight patients with allergic rhinoconjunctivitis were assessed subjectively and objectively using twice-daily symptom scores for nasal (reflective total nasal symptom score [rTNSS] and instantaneous TNSS [iTNSS]) and ocular (reflective total ocular symptom score [rTOSS] and instantaneous TOSS [iTOSS]) symptoms, rhinoconjunctivitis quality-of-life questionnaires (RQOLQs), and acoustic rhinometry. All measurements were taken at baseline and at 4 and 8 weeks of treatment. Sixty-three patients who were randomized into the mometasone furoate group (n = 36) and the fluticasone furoate group (n = 27) completed the study. Seventy-six percent of patients had mild ocular symptoms, 20.5% had moderate symptoms, and only 2.6% had severe symptoms at baseline based on the iTOSS; 65.1% had mild nasal symptoms and 3% had severe nasal symptoms. There was significant reduction in the symptom scores after 1 week (p < 0.05). Both groups had significant improvement in RQOLQ scores after 1 month, which further improved at 2 months (p < 0.05). The nasal dimensions also improved in both groups (p < 0.05) but there was no statistically significant difference between groups. Both mometasone furoate and fluticasone furoate are effective as single-modality treatment of allergic rhinoconjunctivitis. The majority of patients manifest mild ocular symptoms that may be solely treated with intranasal steroids.